The New District of East Belitung: The Review Poliferation Process - YANI, HENDRI (Universitas Muhammadiyah Yogyakarta, 2013)
The regional autonomy conducted in many functions of government. One of its forms isproliferation of region. The aim of this study was to overview the proceed of proliferation inEast Belitung District. This research was a qualitative research consisted of two maintechniques to collect the data; they were interview and secondary data from documentations.The findings show that there were ten steps to create the new East Belitung District. Thesteps started from the preparations of local’s planning and administration to the final steps inthe hand of national parliaments. This study found that the number of local government inIndonesia has increases, and the process at the central government level seem relatively easy.But, the eligibility criteria being compromised. Then, the political will from communitieswere not clear mention. Also there was a conflict interest between local government andcentral government in the feasibility study for proliferation in Belitung District. It concludedthat we could not deny that political intervention in the bureaucracy has facilitated theformation of East Belitung districts.Keywords: proliferation, East Belitung